2008
DOI: 10.1007/s00268-008-9845-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approach to Extensive Hidradenitis Suppurativa in the Perineal/Perianal and Gluteal Regions

Abstract: Conservative treatment methods have little or no effect on extensive perineal/perianal hidradenitis suppurativa. Therefore, total surgical excision must be considered for these patients to prevent further complications, such as abscess, sinus tract formation, fistulization, and scarring. A temporary stoma may be needed in some cases. Because wound management after total excision is performed via different methods according to each individual patient, multidisciplinary team work is necessary and the patients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 47 publications
0
84
1
2
Order By: Relevance
“…The many known consequences of hidradenitis include psychological stress, lymphedema, fistulae, cancer, and even death [2,4,5,[7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The many known consequences of hidradenitis include psychological stress, lymphedema, fistulae, cancer, and even death [2,4,5,[7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…They treated patients with medically refractory hidradenitis and had no recurrences at their operative sites. While medical therapy should be first line treatment, surgical excision is the only curative option, and is often necessary in extensive disease [4,5,7,8,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, wide excision has been extensively demonstrated to offer patients the lowest chance of recurrence and therefore, the highest possibility of cure for HS, particularly when the disease is more severe 29,34]. While wide excision has been confidently shown to offer the best chance at a cure, the most superior method for closure is still under debate.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Though medical management may lead to symptomatic relief, studies have suggested that it is unlikely that these treatments change the natural course of HS [28][29][30]. There are several options for surgical management including incision and drainage, deroofing, local excision with primary closure, and wide excision techniques.…”
Section: Surgical Managementmentioning
confidence: 99%